Conciencia ambiental y prácticas proambientales de visitantes y comerciantes en la conservación paisajística del Puente de Nanay, Loreto, 2024 - Diaz Reyes, Mauro Martin (2025)
The present quantitative study evaluates the influence of the environmental awareness of visitors and merchants on the landscape conservation of the Nanay Bridge during the year 2024. A non-experimental, correlational and transversal design is adopted, with a sample of 148 respondents (96 visitors and 52 merchants) selected through purposive sampling. Data collection was carried out through structured surveys with closed Likert type and dichotomous questions, obtaining a Cronbach's Alpha reliability of 0.897. The inferential analysis included the Kolmogorov-Smirnov test to evaluate the normality of the data and, due to the differences in the distribution of the dimensions evaluated, the Rho Spearman correlation coefficient was applied. The results indicate that the environmental awareness of visitors and merchants significantly influences the landscape conservation of the Nanay Bridge, mainly in the promotion of pro environmental attitudes. However, challenges remain in implementing sustainable practices. It is observed that the majority of respondents present a moderate to high level of environmental awareness, with general knowledge about problems such as pollution. However, gaps in knowledge about environmental regulations and local biodiversity are identified. Regarding environmental practices, although there is provision for adequate waste management, participation in conservation activities is limited. A direct relationship is evident between environmental awareness and pro-environmental practices, but psychological and contextual barriers are also identified that restrict the conversion of knowledge and attitude into concrete actions for the conservation of the environment.